2020
DOI: 10.3390/md18050233
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-Gentamicin Conjugate Hydrogel Promoting Skin Scald Repair

Abstract: Our earlier research indicated that chitosan-gentamicin conjugate (CS-GT) possesses superior antimicrobial activity and good water solubility. To develop CS-GT-based scald dressings, the antibacterial properties of CS-GT were further studied, and the biosafety of CS-GT and the healing mechanism of CS-GT hydrogel was systematically explored in this article. It was found that cell viability shows a declined inclination with the prolonged culture time and the increased concentration of CS-GT. After three day’s cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 46 publications
1
26
0
1
Order By: Relevance
“…On day 14 and 21, the wound healing rate was 89.18% and 99.61%, respectively, in vivo on the animal model treated with the hydrogel. On day 14, complete epidermal regeneration was visible [ 106 ]. Cifuentes et al reported the efficacy of chitosan hydrogels functionalized with either bemiparin or unfractionated heparin for diabetic wound healing.…”
Section: Preparation Techniques and Properties Of Hydrogelsmentioning
confidence: 99%
“…On day 14 and 21, the wound healing rate was 89.18% and 99.61%, respectively, in vivo on the animal model treated with the hydrogel. On day 14, complete epidermal regeneration was visible [ 106 ]. Cifuentes et al reported the efficacy of chitosan hydrogels functionalized with either bemiparin or unfractionated heparin for diabetic wound healing.…”
Section: Preparation Techniques and Properties Of Hydrogelsmentioning
confidence: 99%
“…Our previous research also found that CS-GT-based hydrogels, with antimicrobial activity, cytocompatibility, and hemocompatibility, can accelerate the wound healing of New Zealand rabbits [ 27 ]. Particularly, CS-GT can inhibit pathogenic Escherichia coli , Pseudomonas aeruginosa , and Staphylococcus aureus effectively [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Typically, RL-QN15 was dissolved in PBS solution and the mixed solution's relative concentration was determined via the absorbance at 220 nm determined by a spectrophotometry (NanoDrop One, Thermo, USA). PBS solution containing HPDA (0.5 mg) and RL-QN15 (100 nmol) with a volume of 5 mL was stirred at 4 °C for 24 h to form a nanocomposite solution, then centrifuged (10 000g, 5 min, 4 ℃), and the resulting supernatant was taken at various time-points (2,4,6,8,10,12,16,20, and 24 h) to determine the relative concentration of the unloaded peptide RL-QN15. The loading efficiency of HPDA nanoparticles against RL-QN15 was calculated according to the equation: Loading efficiency (%) = [C (0) − C (2,4,6,8,10,12,16,20,24)] / C (0) × 100, where C (0) represented the initial concentration, and C (2, 4, 6, 8, 10, 12, 16, 20, and 24) represented the concentrations at 2, 4, 6, 8, 10, 12, 16, 20, and 24 h, respectively [19,30].…”
Section: The Determination Of Loading and Slow-releasing Efficiency Of Hpda Nanoparticles Against Rl-qn15mentioning
confidence: 99%
“…As the largest organ of the human body, skin participates in many important physiological functions, such as sweating, fever, and pain perception [ 1 , 2 ]. Skin is also an important barrier between the internal body and external environment, protecting internal organs and tissues from skin rupture caused by physical, mechanical, and chemical factors and infections caused by pathogenic microorganisms [ 3 ].…”
Section: Introductionmentioning
confidence: 99%